1999
DOI: 10.1038/sj.jhh.1000771
|View full text |Cite
|
Sign up to set email alerts
|

Blood lead and blood pressure: evidence from the Health Survey for England 1995

Abstract: Objectives: To examine the relationship between blood lead and blood pressure (BP) and to estimate the possible effects of a decrease in blood lead on BP. Methods: A 2-ml blood sample was collected from a sub-sample of those included in the Health Survey for England 1995, a cross-sectional survey of a nationally representative sample of the adult English population. Blood lead concentration was measured by atomic absorption spectrometry and three BP readings were taken under standardised conditions using the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 20 publications
1
23
0
1
Order By: Relevance
“…It is a known toxic substance that induces adverse health effects in multiple systems, including neurological, hematological and cardiovascular 1,2) . Most studies have indicated that environmental exposure to lead is associated with an increased risk of hypertension [3][4][5][6][7][8][9][10] . Our previous study found a relationship between blood lead level and hypertension among traffic policemen working in the eastern region of Thailand 11) .…”
Section: Introductionmentioning
confidence: 99%
“…It is a known toxic substance that induces adverse health effects in multiple systems, including neurological, hematological and cardiovascular 1,2) . Most studies have indicated that environmental exposure to lead is associated with an increased risk of hypertension [3][4][5][6][7][8][9][10] . Our previous study found a relationship between blood lead level and hypertension among traffic policemen working in the eastern region of Thailand 11) .…”
Section: Introductionmentioning
confidence: 99%
“…Chronic exposure to low levels of lead (Pb 2ϩ ) is known to cause high blood pressure in humans and experimental animals (Harlan, 1988;Schwartz, 1995;Bost et al, 1999;Carmignani et al, 2000;Vaziri and Ding, 2001). Altered endothelial and vascular smooth muscle functions (KhalilManesh et al, 1993;Gonick et al, 1997;Marques et al, 2001) may account in part for the vascular effects of lead.…”
mentioning
confidence: 99%
“…For example, adjusting for alcohol consumption will decrease the apparent association between blood lead concentration and blood pressure, if alcohol consumption contributes to lead intake and, thereby, blood lead concentration (Bost et al 1999;Hense et al 1993;Hertz-Picciotto and Croft 1993;Wolf et al 1995). Conversely, failure to account for important effect modifiers (e.g., inherited disease) will result in overestimation of the apparent strength of the association.…”
Section: Health Effectsmentioning
confidence: 99%
“…Covariate-adjusted risk of ischemic heart disease (OR) was not significantly associated with PbB. PbBs in cases (n=316) of ischemic heart disease were not statistically different, (Bost et al 1999). Multiple seated blood pressure measurements were taken.…”
Section: Health Effectsmentioning
confidence: 99%